2019
DOI: 10.1098/rsos.180527
|View full text |Cite
|
Sign up to set email alerts
|

Photoacclimation and induction of light-enhanced calcification in the mesophotic coralEuphyllia paradivisa

Abstract: Corals and their photosymbionts experience inherent changes in light along depth gradients, leading them to have evolved several well-investigated photoacclimation strategies. As coral calcification is influenced by light (a process described as LEC—‘light-enhanced calcification’), studies have sought to determine the link between photosynthesis and calcification, but many puzzling aspects still persist. Here, we examine the physiology of Euphyllia paradivisa , a coral species found at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
3
12
0
Order By: Relevance
“…Conducting the metabolic measurements under blue light resulted in smoother P-E curves (Supplementary Figure 3), which may represent a more natural performance of mesophotic corals. Most of the previously reported values for P-E derived parameters that we were able to compare to our measurement aligned with the current results (Cooper et al, 2011;Nir et al, 2014;Eyal et al, 2019). The results indicate that mesophotic corals usually present relatively low compensation irradiance ranging between 15 and 96 µmol photons m −2 s −1 as well as low saturating irradiances, ranging between 28 and 80 µmol photons m −2 s −1 leaving a narrow window of light intensities which enable photosynthesis.…”
Section: Speciessupporting
confidence: 91%
See 2 more Smart Citations
“…Conducting the metabolic measurements under blue light resulted in smoother P-E curves (Supplementary Figure 3), which may represent a more natural performance of mesophotic corals. Most of the previously reported values for P-E derived parameters that we were able to compare to our measurement aligned with the current results (Cooper et al, 2011;Nir et al, 2014;Eyal et al, 2019). The results indicate that mesophotic corals usually present relatively low compensation irradiance ranging between 15 and 96 µmol photons m −2 s −1 as well as low saturating irradiances, ranging between 28 and 80 µmol photons m −2 s −1 leaving a narrow window of light intensities which enable photosynthesis.…”
Section: Speciessupporting
confidence: 91%
“…Our measured values of Symbiodiniaceae density are higher than previously reported values in mesophotic corals (Bongaerts et al, 2011;Cooper et al, 2011), however this parameter can greatly vary between species, depth, and light availability [reviewed by Roth (2014)]. Chlorophyll concentration values determined in this study, align with previously reported values ( Lesser et al, 2010;Cooper et al, 2011;Eyal et al, 2019). The latter result also indicates that the brighter color of the yellow morph of G. minor is probably the result of a higher expression of FPs rather than a low algal density or low chlorophyll concentration.…”
Section: Speciessupporting
confidence: 88%
See 1 more Smart Citation
“…Coral growth rates can vary with increasing depth (Baker & Weber, 1975), and this in turn can leave isotopic signals (Patzold, 1984). Further, coral growth rates can vary with light exposure, independent of changes in photosynthesis (Eyal et al ., 2019). Growth signals can also correlate with light exposure in skeletal carbon fractionation (Shimamura et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being found only at depths greater than 36 m in Eilat, this species has demonstrated both a low mortality rate and an ability also to prosper in shallow depths and shallow light environments for prolonged periods of time following transplantation 20 . When the photoacclimatization potential of this species to a shallow light environment was tested 21 , the corals lost their original mesophotic ability to efficiently utilize low-light intensities, but were still able to withstand higher light intensities before suffering from photoinhibition (Ben-Zvi et al . ; in preparation).…”
Section: Introductionmentioning
confidence: 99%